2013
DOI: 10.1039/c2mb25308a
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization and biological properties of human gastrokine 1

Abstract: Gastrokine-1 (GKN1), a protein expressed in normal gastric tissue, but absent in gastric cancer tissues and derived cell lines, has recently emerged as a potential biomarker for gastric cancer. To better establish the molecular properties of GKN1, the first protocol for the production of mature human GKN1 in the expression system of Pichia pastoris was settled. The recombinant protein showed anti-proliferative properties specifically on gastric cancer cell lines thus indicating that it was properly folded. Cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 53 publications
1
20
0
Order By: Relevance
“…To accomplish this deficiency, we have recently reported the characterization and secondary structural properties of human recombinant GKN1 (rGKN1). Using bio-informatics tools, we found that GKN1 BRICHOS domain has structural features similar to those endowed by BRI-CHOS domain-containing protein family [8]. In particular, predicted GKN1 3D models suggested a structural organization of its BRICHOS domain resembling that of the corresponding BRICHOS domain of prosurfactant protein C (proSP-C), a trans membrane (TM) protein expressed in epithelial type II cells.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…To accomplish this deficiency, we have recently reported the characterization and secondary structural properties of human recombinant GKN1 (rGKN1). Using bio-informatics tools, we found that GKN1 BRICHOS domain has structural features similar to those endowed by BRI-CHOS domain-containing protein family [8]. In particular, predicted GKN1 3D models suggested a structural organization of its BRICHOS domain resembling that of the corresponding BRICHOS domain of prosurfactant protein C (proSP-C), a trans membrane (TM) protein expressed in epithelial type II cells.…”
Section: Introductionmentioning
confidence: 91%
“…Human GKN1 is made of 185 amino acids containing a 20 amino acid extracellular signal peptide localized in the N-terminal region [1]. The protein is characterized by the presence of a central structural BRICHOS domain [7] of about 100 amino acids containing two conservative cysteine residues most likely involved in disulfide bridges [8]. The association of GKN1 BRICHOS domain with biological functions has been proposed but not yet ascertained.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, also the 3D model of GKN1 BRICHOS domain constructed at Swiss Model Server 11 shows a structural organization approaching that of the corresponding domain of proSP-C 13 . Both ProSP-C and BRI2 are membrane proteins containing a region with a tendency to form β-sheet structures that can be proteolytically cleaved with mechanisms still unclear.…”
Section: Gkn1 and The Anti-amyloidogenic Property Of Brichos Domainmentioning
confidence: 99%
“…The first two conserved cysteines (C 95 and C 156 ), are present in all BRICHOS domains, whereas the other two cysteines (C 179 and C 193 ), are conserved in all other mammalian gastrokines. In the case of human GKN1, the two latter cysteines are also involved in disulfide bridge as determined by mass spectrometry (MS) performed on rGKN1 11 ( Figure. 2).…”
Section: Gkn1 and The Anti-amyloidogenic Property Of Brichos Domainmentioning
confidence: 99%
See 1 more Smart Citation